Transfer of liquid and water vapour through knitted materials: Original scientific paper - Petrov, Antonija; Čubrić, Goran; Salopek Čubrić, Ivana (HEMIJSKA INDUSTRIJA (Chemical Industry), 2023)
Active sportswear has certain functions that should meet the expected properties and improve the performance of athletes. In addition to functionality, an important aspect of sportswear is thermal and physiological comfort. By choosing the right clothing for athletes, the dynamic and thermal load can be significantly reduced because sports require unhindered mobility, and clothing must be adapted to the body and absorb sweat. Proper vapour and liquid flow in textile materials are important from a comfort point of view. Therefore, in this research, seven representative samples were selected that are used for clothing intended for sport and leisure. Using an infrared thermal camera, the transfer of liquid on the surface of the material was precisely monitored, until the final stage when the material is completely dry. The obtained results show that fabric made of 100 % polyester has the shortest drying time, while the highest vapour permeability was exhibited by fabric made of viscose and elastane yarn. Those fabrics should be considered as the most suitable for sportswear because they do not cause discomfort when worn. Infrared thermography is a very useful method in research because it provides reliable data, especially when it comes to the drying time of the material.